The management of waqf universities in Selangor, Malaysia / Mohd. Ali Muhamad Don and Muhamad Rahimi Osman - Muhamad Don, Mohd. Ali; Osman, Muhamad Rahimi (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2020)
In Malaysia, waqf management including those in universities, is under the authority of the State Islamic Religious Council as a sole trustee waqf. This is to protect the waqf assets from any interventions by the heirs. Even so, one Malaysian university is said to manage the waqf scheme without the supervision of the Islamic Council which contradict with the provision of the State of Islamic Religious Council (SIRC) as the sole trustee of waqf. Thus, this study explores the management of waqf by several universities in Selangor and relation to SIRC as the sole trustee of waqf. A qualitative research approach was employed to collect data from focus group discussions and interviews with selected participants from the Selangor Islamic Religious Council (Selangor IRC), selected universities and waqf experts in Malaysia. The findings show that University Kebangsaan Malaysia and University Putra Malaysia waqf funds are managed under the Selangor IRC monitoring while University Islam Antarabangsa Malaysia endowment or waqf fund is managed privately by the university. The impact of this is that several waqf management issues arose. Hence, the authors recommend the Model theory of al-wilayah to be applied in the management of waqf in the universities. Through this model, SIRC and the university can play a more significant role in the management of waqf, thereby promoting the development of waqf in Malaysia.